Responding to Islamophobia by Internalizing the Value of Islam Rahmatan lil Alamin through Using the Media - Muhamad Parhan; Mohammad Rindu Fajar Islamy; Nurti Budiyanti; Risris Hari Nugraha; Pandu Hyangsewu (Islam Realitas: Journal of Islamic and Social Studies, 2020)
This article focuses on an inaccurate understanding of Islam that causes hatred, anxiety, and unfounded fear of the Muslim community. On account of this view of Islam, Muslims face hostility, discrimination, intolerance, and racism. This attitude is increasingly seen in mass media propaganda that presents a partial and inaccurate view of the religion. Islam is presented as a violent belief system and is responsible for radicalism and terrorism. The media greatly influences social reality. They function as a spectacle, but they also influence public opinion on a range of issues. The research design of this paper uses literature review with descriptive analysis. The results show that internalizing the Islamic value of rahmatan lil alamin (“being a mercy to the world”) through the media is a solution that can rectify misconceptions about Islam. Along with the foundation of amar ma’ruf nahi munkar (“enjoining the good and forbidding the evil”), the value of “being a mercy to the world” can transform people into educators (muaddib), agents of correct information (musaddid), reformers (mujaddid), unifiers (muwahhid), and fighters (mujahid). Artikel ini fokus terhadap pemahaman Islam dengan perspektif yang salah, sehingga menimbulkan kebencian, kecemasan, dan ketakutan yang tidak berdasar serta berlebihan kepada individu maupun komunitas Islam. Akibatnya timbul permusuhan, diskriminasi, intoleransi, dan rasisme. Sikap ini semakin terlihat melalui propaganda media massa yang menampilkan kontroversi yang tidak benar dan parsial terhadap Islam, media merepresentasikan Islam dengan kekerasan dan radikal melalui fenomena terorisme. Kehadiran media sangat berpengaruh terhadap realitas sosial yang tidak hanya berfungsi sebagai tontonan tetapi menjadi tuntunan yang menggiring opini publik dalam merubah sikap, pandangan, dan perilaku. Desain penelitian menggunakan literature review dengan analisis deskriptif. Hasil penelitian menunjukkan bahwa Internalisasi nilai-nilai Islam rahmatan lil alamin melalui media merupakan solusi dalam meluruskan pemahaman yang keliru tentang Islam, yang berfungsi sebagai pendidik (muaddib), agen informasi yang benar (musaddid), menjadi pembaharu (mujaddid), pemersatu (muwahhid), dan pejuang (mujahid) dengan dasar amar ma’ruf nahi munkar.